Implikasi Integritas bagi Guru Kristen - Dewi, Ester Yunita; Sailendra, Arthinda Arthur (Sekolah Tinggi Teologi Kadesi Bogor, 2024)
Integrity is a term that has become familiar because everyone in all professionsstrives to have good integrity, including Christian teachers. The integrity that people pursueand possess is generally the same as the integrity that Christian teachers also pursue andpossess. Problems related to integrity arise, because there are cases found both in the massmedia or social media and in the community regarding teacher integrity. Teachers who donot maintain integrity can damage their own reputation as a teacher. Teachers who areeducated individuals and certainly know the need for integrity within themselves. However,even though we know that integrity is good and must be possessed, it cannot be denied thatthere are teachers who deliberately ignore it for the sake of certain interests. The results ofresearch on the implications of the integrity of Bible figures for Christian teachers are asfollows: First, integrity is a characteristic possessed by someone who has been able todevelop his personality in such a way as to achieve a high level of development, balancedand integrated between various aspects of himself: physical, psychological, social andspiritual. Integrity can be interpreted as honesty and conformity between values andbehavior. Values and behavior will be compatible if spirituality leads the behavior. Second,the definition of integrity is very perfect and it is impossible for humans to have it, but if youpay close attention, Daniel, Paul, Ruth, Barnabas and several other Bible figures can havegood integrity. Third, nothing is impossible for a Christian teacher, especially with sincerity,surrender and offering it for the glory of God's name. Have commitment and consistency andmaintain honesty and conformity between values and behavior based on the truth of God'sword. The Holy Spirit will give strength and sensitivity so that we can maintain a balance ofbelief between words and deeds.